Migrazione in adolescenza ed esordio psicotico: psicopatologia e fattori di rischio - Battaglia, Claudia (Il sogno della farfalla, 2018)
The article focuses on the phenomenon of the migration of adolescents and the psychopathology that is associated with it. Immigrant adolescents, due to the very complex period of their life they are going through, and the stressful events they are exposed to, are at a higher risk of developing psychological disorders. A recent meta-analysis has shown statistically significant differences in terms of the risk to develop psychosis amongst first and second-generation migrants. These data oblige us to consider the role of post-migration factors to a greater extent than what we have done so far.